Content and implementation of clinical decisions in the routine care of people with severe mental illness. (February 2015) - Konrad, Jana; Loos, Sabine; Neumann, Petra; Zentner, Nadja; Mayer, Benjamin; Slade, Mike; Jordan, Harriet; De Rosa, Corrado; Del Vecchio, Valeria; Égerházi, Anikó; Nagy, Marietta; Krogsgaard Bording, Malene; et al.
Abstract Background: Clinical decision making (CDM) in the treatment of people with severe mental illness relates to a wide range of life domains. Aims: To examine content of CDM in mental health care from the perspectives of service users and staff and to investigate variation in implementation of decisions for differing content. Method: As part of the European multicenter study clinical decision making and outcome in routine care for people with severe mental illness (ISRCTN75841675), 588 service users and their clinicians were asked to identify the decisions made during their last meeting. Decisions were then coded into content categories. Two months later, both parties reported if these decisions had been implemented. Results: Agreement between patients and staff regarding decision making was moderate (κ = 0.21–0.49; p < 0.001). Decisions relating to medication and social issues were most frequently identified. Overall reported level of implementation was 73.5% for patients and 74.7% for staff, and implementation varied by decision content. Conclusions: A variety of relevant decision topics were shown for mental health care. Implementation rates varied in relation to topic and may need different consideration within the therapeutic dyad.